Potential role of MAP2K1 mutation in the trans-differentiation of interdigitating dendritic cell sarcoma: Case report and literature review - Jenei, Alex; Bedics, Gábor; Erdélyi, Dániel J.; Müller, Judit; Györke, Tamás; Bödör, Csaba; Szepesi, Ágota (Frontiers in Pediatrics, 2022)
A 5-year-old male child was diagnosed with interdigitating dendritic cell sarcoma (IDCS) during the maintenance therapy for acute precursor B-cell lymphoblastic leukemia (B-ALL). Multiplex lymph node involvements of the neck were found by Positron Emission Tomography-Computed Tomography (PET-CT). Treatment including surgical and chemotherapy resulted in complete remission. Four years later, systemic bone infiltration was discovered. Surgical resection of the IV. rib and intensive chemotherapy led to complete morphological remission and allogeneic bone marrow transplantation was performed. Comprehensive genomic profiling of the formalin fixed tumor tissue and the cryopreserved leukemic cells revealed several common alterations and divergent clonal evolution with a novel MAP2K1 mutation of the IDCS, potentially responsible for the trans-differentiation of the common lymphoid-committed tumor progenitor.